Viral Hepatitis: Chronic Hepatitis B (Springer International Publishing, 2018)
This book presents up-to-date, practically oriented information on major topics in chronic hepatitis B. The coverage encompasses epidemiology; diagnosis, including molecular methods; treatment and challenges; and the management of co-infections. Readers will also find guidance on the invasive and non-invasive assessment of fibrosis in HBV infection and the prevention of mother-to-child transmission of HBV. Management of chronic hepatitis B in children is considered separately, and emerging drugs that hold promise for the treatment of chronic HBV infection are discussed. Chronic Hepatitis B will be of high value for general practitioners and specialists in gastroenterology, infectious diseases, and internal medicine. It will be international in scope in terms of both authorship and appeal.